2018
DOI: 10.1186/s13014-018-1187-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VMAT-IMRT compared to 3D conformal radiotherapy on anal sphincter dose distribution in neoadjuvant chemoradiation of rectal cancer

Abstract: BackgroundNeoadjuvant radio- or chemoradiation (nIRT) therapy is the standard treatment for loco-regional advanced rectal cancer patients of the lower or middle third. Currently, intensity modulated radiation therapy (IMRT) is not the recommended radiation technique even though IMRT has advantages compared to 3D-radiation regarding dose sparing to organs at risk like small bowel and urinary bladder. So far, the benefit of IMRT concerning the anal sphincter complex is not examined. With this study we intended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[ 7 9 ] Comparison of 3-dimensional conformal radiation therapy (3D-CRT) and IMRT showed better sparing of OARs, dosimetric results, and target coverage in favor of IMRT; therefore, IMRT has become the standard radiation technique in pelvis located cancers. [ 10 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 9 ] Comparison of 3-dimensional conformal radiation therapy (3D-CRT) and IMRT showed better sparing of OARs, dosimetric results, and target coverage in favor of IMRT; therefore, IMRT has become the standard radiation technique in pelvis located cancers. [ 10 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although results from comparative randomized clinical trial are not available yet, IMRT is usually associated with less dose to organ at risk, such as urinary bladder, small bowel and anal sphincters (in selected cases). This is translated into better clinical outcomes, in terms of gastrointestinal toxicity, genitourinary toxicity and skin side effects [1620].…”
Section: Methodsmentioning
confidence: 99%
“…A previous meta-analysis of 859 patients from six studies showed that IMRT was associated with lower incidences of ≥ grade 3 acute overall gastrointestinal toxicity, diarrhea, and proctitis compared with 3DCRT [8]. Compared with conventional chemoradiotherapy, IMRT can also signi cantly reduce the dose distribution to the anal sphincters for patients with rectal cancer [13]. Whether IMRT can decrease the dose distribution to proximal resection margins and radiation injuries need further studies.…”
Section: Discussionmentioning
confidence: 99%